2014
DOI: 10.1242/jcs.152173
|View full text |Cite
|
Sign up to set email alerts
|

p75NTR-dependent Rac1 activation requires receptor cleavage and activation of an NRAGE and NEDD9 signaling cascade

Abstract: The p75 neurotrophin receptor (p75NTR, also known as tumor necrosis factor receptor superfamily member 16) is implicated in diverse cellular events, but fundamental aspects of its signaling mechanisms remain unclear. To address this, we have established a novel bioassay to characterize signaling cascades activated by p75NTR. We show that in COS7 cells, p75NTR expression causes a large increase in cell surface area that relies on the activation of Rac1, and we demonstrate that the p75NTR-dependent COS7 phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Depletion of VAV2 was observed and that could impair the ability of NEDD9 to activate Rac1 [34]. In another study using a yeast two-hybrid screen, NEDD9 was also reported to mediate p75NTR-dependent Rac1 activation leading to cell spreading [35]. Therefore, it may be reasonable to speculate that the effect of NEDD9 on breast cancer cell migration is mediated by Rac1.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of VAV2 was observed and that could impair the ability of NEDD9 to activate Rac1 [34]. In another study using a yeast two-hybrid screen, NEDD9 was also reported to mediate p75NTR-dependent Rac1 activation leading to cell spreading [35]. Therefore, it may be reasonable to speculate that the effect of NEDD9 on breast cancer cell migration is mediated by Rac1.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, it is unlikely that the channels were activated by G q -coupled neurotransmitter receptor-mediated mechanisms, as these cause the hydrolysis of PIP 2 and inhibit channel activity (Raveh et al, 2010 ), with PIP 2 being required for GIRK channel opening. Several groups have previously reported that p75 NTR can increase PIP 2 levels via Rac1 (Gibon et al, 2015 ; Zeinieh et al, 2015 ), a necessary step for GIRK channel activation by p75 NTR (Coulson et al, 2008 ). We therefore suggest that p75 NTR mediates pathological GIRK channel activity subsequent to Aβ-induced channel upregulation, nominally ~2–3 h after Aβ application.…”
Section: Discussionmentioning
confidence: 99%
“…However, in all cases, the p75NTR fl/fl ; Atoh1 Cre mice showed delayed cell cycle exit compared with WT. p75NTR can regulate RhoA (Yamashita et al, 1999;Yamashita and Tohyama, 2003) and rac1 (Harrington et al, 2002;Zeinieh et al, 2015) activity in different contexts. p75NTR is expressed in all the proliferating GCPs in the external EGL, making this receptor a potential candidate to directly regulate the GCP cell cycle.…”
Section: P75ntr Regulates Cell Cycle Lengthmentioning
confidence: 99%